Women of Assur and Kanesh texts from the archives of Assyrian Merchants - Michel, Cécile 1962- (Atlanta Society of Biblical Literature, 2020)
Cover -- Contents -- Series Editor's Foreword -- Acknowledgements -- Abbreviations and Conventions -- List of Figures -- Map of the Old Assyrian Period -- Introduction -- Chronology, Calendars, and Metrology -- Marriage and Divorce -- Women and Family -- Housewives -- Businesswomen -- Religion and Social Mores -- Portraits of Assyrian and Anatolian Women -- Texts Edited -- Bibliography -- Indexes.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books